Salmonelas e coliformes fecais em águas de bebida para animais - Souza, L. C. de; Iaria, S. T.; Paim, G. V. (FapUNIFESP (SciELO), 1992)
Sixty small farms of Botucatu County, S. Paulo, Brazil, given over to cattle breeding were studied. These farms account for 15% of the total of 402 farms that exist in the county. The sample was drawn by simple probabilistic technique. There were found to be one hundred and thirteen drinking places located on the farms. Samples of water were taken from these drinking places and examined for bacteria of the genus Salmonella, for the determination of Most Probable Number (MNP) of fecal coliform bacteria as well as determination of the water's pH. Water temperature was measured before collection. Samples from 15 drinking places (13.3%) were positive for Salmonella. The drinking places belonged to 12 of the sixty farms studied (20%). The following serotypes were identified: S. dublin, S. newport, S. madelia, S. IV 43:g,z57:-, S. saphra, S. glostrup, S. IV ochsenzool; S. I9,12:i:- and two new serotypes S. IV 41:z52:- and S. IV 50:d:-. Of the 113 samples studied 14 (12.4%) presented MPN/100ml of fecal coliforms above 4,000. There was no relationship between MPN/100ml of fecal coliforms above 4,000 and positivity for Salmonella. Highest positivity both for Salmonella and MPN/100mL of fecal coliforms over 4,000 occurred at temperatures above 18 degrees C. As regards pH, in both situations the highest positivity occurred between 6.0 and 7.0.
Salmonellas and fecal coliforms in drinking water for animals
Keywords: water; animal; animal husbandry; Brazil; Enterobacteriaceae; feces; health; isolation and purification; microbiology; Salmonella; Animal; Animal Husbandry; English Abstract; Feces; Rural Health; Water; Water Microbiology